Rekomendasi Dan Tinjauan Struktur Kurikulum Pengajaran dan Model Pembelajaran Pendidikan Kewarganegaraan Di Negara Nigeria - Sutanto, Zulkifli Alamsah (Faculty of Teacher Training and Education of Undaris, 2025)
This study aims to analyze various recommendations for Civic Education in terms of curriculumstructure, content, teaching, and learning models in Nigeria. The research uses a literature review method,which seeks to explore various theories related to the research topic as a reference for the findings. Theprocess includes data collection, data analysis, and drawing conclusions. The data were obtained bycollecting books and journals from national and international sources such as Google Scholar, Taylor andFrancis, and other reliable sources. The data analysis used critical appraisal, which involves analyzing theselected journals to identify differences, similarities, and limitations among them. The results of the studyare: 1) In terms of curriculum structure, Civic Education in Nigeria is organized by educational levels. Atthe primary and secondary levels, it focuses on social studies and health issue s, while at the university level,Civic Education is taught as a general course covering political science, government and democratic. 2)Teaching in Nigeria is conducted by teachers according to their subject and grade level. In addition, moreexperienced and older teachers tend to better support diversity in their classrooms. 3) The learning modelused in Civic Education in Nigeria applies a holistic approach.Keywords: Nigeria, Learning Model, Civic Education, Teaching, Curriculum Structure